Anonymous

# The price elasticity of demand for a linear demand function, D(p)=b−ap is given by Q=E(p)=(ap)/(b-ap)?

Rewrite the formula to express price as a function of elasticity

p=g(Q)=?

Update:

b) What is the long-term behavior of g?

As elasticity increases without bound, the price at which this elasticity occurs approaches

### 1 Answer

Relevance

- BryceLv 71 month ago
E= ap/(b - ap)

Eb - Eap= ap

Eap + ap= Eb

p(Ea + a)= Eb

p= g(Q)= Eb/(Ea + a)= Eb/[a(E + 1)]

As E→∞, p→b/a

- Login to reply the answers

Still have questions? Get your answers by asking now.